Roles of peripheral immune cells in the recovery of neurological function after ischemic stroke - Zhang, Zhaolong; Lv, Mengfei; Zhou, Xin; Cui, Yu (Frontiers in Cellular Neuroscience, 2022)
Stroke is a leading cause of mortality and long-term disability worldwide, with limited spontaneous repair processes occurring after injury. Immune cells are involved in multiple aspects of ischemic stroke, from early damage processes to late recovery-related events. Compared with the substantial advances that have been made in elucidating how immune cells modulate acute ischemic injury, the understanding of the impact of the immune system on functional recovery is limited. In this review, we summarized the mechanisms of brain repair after ischemic stroke from both the neuronal and nonneuronal perspectives, and we review advances in understanding of the effects on functional recovery after ischemic stroke mediated by infiltrated peripheral innate and adaptive immune cells, immune cell-released cytokines and cell‒cell interactions. We also highlight studies that advance our understanding of the mechanisms underlying functional recovery mediated by peripheral immune cells after ischemia. Insights into these processes will shed light on the double-edged role of infiltrated peripheral immune cells in functional recovery after ischemic stroke and provide clues for new therapies for improving neurological function.